Éloge de la traduction - Shimizu, Toru (Meta, 1988)
SummaryThis article is the written text of a presentation made at a workshop on cooperation between authors and their translators at a symposium in Nice in November 1983 on the subject "French, a foreign language". Part of the author's ideas are based on his experience in translating the works of Michel Butor.Language imposes a certain vision of the world on speakers, but not in a rigid and non-modifiable way. In this respect, translation has always played and continues to play an important role in shaping Japanese culture through experimentation with new styles and new approaches. In Japan, translation of literature is considered as participation in literary creation : most translations of literary and theoretical texts are done by academics, critics and writers, and the translated text of a book is generally followed by a rather long essay by the translator. In France, translators are generally not considered as literary personalities and their social status is accordingly low, in spite of a number of significant exceptions. And yet, translation forces one to innovate conceptually and linguistically, and therefore culturally; hence the positive nature of its contribution to the host culture, in particular through cooperation between authors and their translators.